Tailoring a digital psychological intervention for adolescents with chronic pain (WebMAP Mobile) and co- morbid insomnia symptoms. - De la Vega, Rocío; Law, Emily; Daniels, Kristen; Palermo, Tonya M (My University, 2021)
Introduction. Insomnia is common in youth with chronic pain (CP), and is associated with reduced quality of life and higher pain interference. Although psychological interventions for CP may include sleep hygiene education, typically they do not specifically target insomnia. Offering additional interventions to meet the individual treatment needs of those with insomnia may increase treatment benefit. Methods. This was a hybrid effectiveness-implementation cluster randomized controlled trial conducted in 8 specialty clinics, comparing WebMAP Mobile (WMM) vs usual care. Participants were 143 youth (10-17 years old, Mage=14.5; 80% female) with CP, from which 73 were randomized to WMM. Two items from the Adolescent Sleep Wake Scale were administered during the app set up and participants with problems falling or staying asleep were automatically assigned an additional module which included stimulus control and sleep restriction techniques to reduce insomnia symptoms. Chi2 tests were conducted to test for changes in the insomnia classification according to the Insomnia Severity Index (no insomnia, subthreshold, clinical moderate and clinical severe) from baseline to 3-months follow-up. Results. Most youth, 40(58%), met threshold criteria to receive the additional module and 22% completed it in full. Participants receiving it significantly reduced their insomnia symptoms. Specifically: 11% worsened, 40% showed no change and 49% improved (N=35; Chi2=13.248(6), P=0.04), as compared to those not receiving it: 22% worsened, 48% showed no change and 30% improved (N=27; Chi2=3.897 (6), P=069. Conclusions. Adding an insomnia module was effective decreasing insomnia symptoms in a sample of youth with CP. Further research evaluating the effectiveness of tailoring interventions is needed to optimize treatments for youth who have common physical and mental health comorbidities such as insomnia.
Keywords: Adolescentes - Enfermedades - Tratamiento; Insomnio - Tratamiento; Aplicaciones informáticas; Pain; Adolescents; CBT; Digital health; Insomnia